MICROSTRUCTURE OF SPLEEN AFTER THE LORATADINE APPLICATION - Дудок, О.В. (World of Medicine and Biology, 2015)
The aim of present investigation was to study morphological changes in the spleen of rats induced by antihistamine drug Loratadine. It was revealed that oral administration of Loratadine caused detectable changes in the vascular stromal components and in the white pulp of spleen. Materials and methods. Experiments were performed on 18 mature white male Wistar rats weighing 160-200g, which were kept in standard vivarium dietary conditions. All manipulations were carried out considering the rules of the European Convention for the protection of vertebrate animals used for experimental and other scientific purposes (Strasbourg, 1986) supplemented by ethical principles of animal experimentation, approved by the First Ukrainian National Congress on Bioethics (2001). The experimental animals were divided into two groups of 9 rats in each. The first group included control animals. Rats of the second group once a day during 30 days were administered orally an antihistamine drug Loratadine at a dose of 0.15 mg / kg body weight, in the form of an aqueous suspension. Results on early stages of experiment (day 10 after the cessation of Loratadine administration) significant changes were detected in the red pulp, including plethora, cellular infiltration of splenic stroma. On the later terms (30-th day of experiment), the changes included increased relative weight of the white pulp with simultaneous inhibition of morphologic manifestations of antigenic stimulation. Analyzing the results in general it should be noted that the use of Loratadine leads to significant disruption of the spleen structures and, consequently, changes in its functional activity.Conclusions: 1. Administration of antihistamine drug Loratadine leads to changes in the morphology of the spleen, which encompass alterations in vascular-stromal and lymphoid cells interactions. 2. Loratadine administration causes an increase in the total volume of the splenic white pulp with degredation of morphological manifestations of its antigenic stimulation.